Lack of TCF2/vHNF1 in mice leads to pancreas agenesis - Haumaitre, C. (National Academy of Sciences, 2005)
Heterozygous mutations in the human POU-homeobox TCF2 (vHNF1, HNF1β) gene are associated with maturity-onset diabetes of the young, type 5, and abnormal urogenital tract development. Recently, pancreas atrophies have been reported in several maturity-onset diabetes of the young type 5 patients, suggesting that TCF2 is required not only for adult pancreas function but also for its normal development. Tcf2-deficient mice die before gastrulation because of defective visceral endoderm formation. To investigate the role of this factor in pancreas development, we rescued this early lethality by tetraploid aggregation. We show that TCF2 has an essential function in the first steps of pancreas development, correlated with its expression domain that demarcates the entire pancreatic buds from the earliest stages. Lack of TCF2 results in pancreas agenesis by embryonic day 13.5. At earlier stages, only a dorsal bud rudiment forms transiently and expresses the transcription factors Ipf1 and Hlxb9 but lacks the key transcription factor involved in the acquisition of a pancreatic fate, Ptf1a, as well as all endocrine precursor cells. Regional specification of the gut also is perturbed in Tcf2(-/-) embryos as manifested by ectopic expression of Shh and lack of Ihh and Ipf1 in the posterior stomach and duodenum. Our results highlight the requirement of Tcf2 for ensuring both accurate expression of key regulator molecules in the stomach–duodenal epithelium and proper acquisition of the pancreatic fate. This study provides further insights into early molecular events controlling pancreas development and may contribute to the development of cell-replacement strategies for diabetes.